The Effect of Social Assistance on the Health Conditions of the Elderly Case Study Analysis of the National Social and Economic Survey - Gusmastuti, Nugrohoning; Widyawati, Diah (Future Science, 2024)
The global population will soon be in the aging phase due to the rapid growth of the elderly population aged 60 years and over. The biggest problems experienced by the elderly group are health problems and economic problems. So that the elderly, especially the poor, need not only health insurance, but also cash and non-cash social assistance to maintain and improve their health conditions. This study aims to determine how the effect of social assistance received by the household on the health condition of the elderly in the household. The method used in this research is descriptive analysis and quantitative analysis with bivariate probit model. The data used is cross sectional data from the March 2021 National Social and Economic Survey. The results show that social assistance PKH has negative effect on the health problem condition of the elderly. Meanwhile, the other independent variables showed that they also has negative effect on the health problem condition of the elderly, such as housing conditions, education, the ratio of hospital beds to the population, and the characteristics of the head of the household.